Twenty four hour pulse pressure predicts long term recurrence in acute stroke patients. Issue 10 (16th September 2005) - Tsivgoulis, G; Spengos, K; Zakopoulos, N; Manios, E; Xinos, K; Vassilopoulos, D; Vemmos, K N
Abstract : Objectives: The impact of different blood pressure (BP) components during the acute stage of stroke on the risk of recurrent stroke is controversial. The present study aimed to investigate by 24 hour BP monitoring a possible association between acute BP values and long term recurrence. Methods: A total of 339 consecutive patients with first ever acute stroke underwent 24 hour BP monitoring within 24 hours of ictus. Known stroke risk factors and clinical findings on admission were documented. Patients given antihypertensive medication during BP monitoring were excluded. The outcome of interest during the one year follow up was recurrent stroke. The Cox proportional hazard model was used to analyse association of casual and 24 hour BP recordings with one year recurrence after adjusting for stroke risk factors, baseline clinical characteristics, and secondary prevention therapies. Results: The cumulative one year recurrence rate was 9.2% (95% CI 5.9% to 12.3%). Multivariate Cox regression analyses revealed age, diabetes mellitus, and 24 hour pulse pressure (PP) as the only significant predictors for stroke recurrence. The relative risk for one year recurrence associated with every 10 mm Hg increase in 24 hour PP was 1.323 (95% CI 1.019 to 1.718, p = 0.036). Higher casual PP levels were significantly related to an increased risk of one year recurrence on univariate analysis, but not in the multivariate Cox regression model. Conclusions: Elevated 24 hour PP levels in patients with acute stroke are independently associated with higher risk of long term recurrence. Further research is required to investigate whether the risk of recurrent stroke can be reduced to a greater extent by decreasing the pulsatile component of BP in patients with acute stroke.